Forgotten People: Poverty, Risk and Social Security in Indonesia - . Nooteboom, G. (Brill, 2015)
In Forgotten People Gerben Nooteboom describes and analyses the livelihoods and social security of peasants and migrant Madurese. It offers a new way to categorise and analyse livelihood security of marginal people in Indonesia by using the concept of style.
English
Keywords: Asian history; indonesia; Cattle; East Kalimantan; Kalimantan; Madura Island; Madurese people; Rice; Samarinda